Phase II randomised control feasibility trial of a nutrition and physical activity intervention after radical prostatectomy for prostate cancer - Jayne V Woodside; Richard M Martin; Raj Persad; Paul Abrams; J Athene Lane; Lucy E Hackshaw-McGeagh; Chris Penfold; Ellie Shingler; Luke A Robles; Claire M Perks; Jeff M P Holly; Edward Rowe; et al. (BMJ Open)
Objective Dietary factors and physical activity may alter prostate cancer progression. We explored the feasibility of lifestyle interventions following radical prostatectomy for localised prostate cancer.Design Patients were recruited into a presurgical observational cohort; following radical prostatectomy, they were offered randomisation into a 2×3 factorial randomised controlled trial (RCT).Setting A single National Health Service trust in the South West of England, UK.Participants Those with localised prostate cancer and listed for radical prostatectomy were invited to participate.Randomisation Random allocation was performed by the Bristol Randomised Trial Collaboration via an online system.Interventions Men were randomised into both a modified nutrition group (either increased vegetable and fruit, and reduced dairy milk; or lycopene supplementation; or control) and a physical activity group (brisk walking or control) for 6 months.Blinding Only the trial statistician was blind to allocations.Primary outcome measures Primary outcomes were measures of feasibility: randomisation rates and intervention adherence at 6 months. Collected at trial baseline, three and six months, with daily adherence reported throughout. Our intended adherence rate was 75% or above, the threshold for acceptable adherence was 90%.Results 108 men entered the presurgical cohort, and 81 were randomised into the postsurgical RCT (randomisation rate: 93.1%) and 75 completed the trial. Of 25 men in the nutrition intervention, 10 (40.0%; 95% CI 23.4% to 59.3%) adhered to the fruit and vegetable recommendations and 18 (72.0%; 95% CI 52.4% to 85.7%) to reduced dairy intake. Adherence to lycopene (n=28), was 78.6% (95% CI 60.5% to 89.8%), while 21/39 adhered to the walking intervention (53.8%; 95% CI 38.6% to 68.4%). Most men were followed up at 6 months (75/81; 92.6%). Three ‘possibly related’ adverse events were indigestion, abdominal bloating and knee pain.Conclusions Interventions were deemed feasible, with high randomisation rates and generally good adherence. A definitive RCT is proposed.Trial registration number ISRCTN 99048944.